Production of virgin coconut oil via water soluble materials and centrifugation method - Khoo, Choon Gek (2012)
The traditional ways of breaking Virgin Coconut Oil (VCO) using fermentation and heating are disadvantageous from both economic and environmental perspectives.In this study,the potentials of the water soluble,oil soluble materials that are environmentally friendly materials and centrifugation methods in demulsification of Virgin Coconut Oil (VCO).The effect of alcohols (methanol and ethanol) added to demulsification via water soluble material and centrifugation methods were also investigated.The study began with some characterization studies to provide understandings of fundamental issues such as formation, formulation and breaking of emulsions.The aim was to obtain optimized operating conditions as well as fundamental understanding of oil-in-water emulsion stability upon which further developing on demulsification process that could be developed.It was found that emulsion demulsification was related to some parameters such as water soluble concentration(0.5 v/v %),centrifugation speed (2,000 – 8,000 rpm) and processing time (30 – 90 minutes).Experimental results found that centrifugation method can enhance the demulsification in a very short time compared to the conventional fermentation method.The results obtained in this study have exposed the capability of centrifugation method in demulsification of Virgin Coconut Oil (VCO) emulsion.Further works are nevertheless required to provide deeper understanding of the mechanisms involved to facilitate the development of an optimum emulsion breaking system applicable to the industry.